%%\dfrac{\tfrac{26^2}{26^8}}{\tfrac{13^{-3}}{13^3}}%%

%%\dfrac{\tfrac{26^2}{26^8}}{\tfrac{13^{-3}}{13^3}}%%

Verwende das Potenzgesetz %%\frac{a^x}{a^y}=a^{x-y}%% auf die Basis %%26%% an.

%%=\dfrac{26^{-6}}{\tfrac{13^{-3}}{13^3}}%%

Verwende das Potenzgesetz %%\frac{a^x}{a^y}=a^{x-y}%% auf die Basis %%13%% an.

%%=\dfrac{26^{-6}}{13^{-6}}%%

Verwende das Potenzgesetz %%\frac{a^x}{b^x}=\left( \frac{a}{b} \right)^x%%.

%%=\left( \dfrac{26}{13} \right)^{-6}%%

Fasse die Basis zusammen.

%%=2^{-6}%%